Analyzing Important Knowledge Management Sub-Processes, Mechanisms, and Technologies in PT XYZ using Contingency View of Knowledge Management - Astrianty, Rani Aprilia; Sensuse, Dana Indra; Imanuddin, Kamila Alifia (Universitas Dharma Wacana, 2024)
In the current competitive business landscape, having knowledge is crucial for gaining a competitive advantage, particularly in service-oriented firms where it significantly enhances organizational capabilities. However, effectively implementing knowledge management presents challenges for companies, as demonstrated by PT XYZ. The main challenges faced by PT XYZ include insufficient information dissemination among departments, complexities in accessing crucial business process information, resulting low level of employee knowledge, contributing to operational inefficiencies. By applying contingency factors theory, this study aims to prioritize essential KM processes at PT XYZ and recommend appropriate KM mechanisms and technologies for implementationThe research, which draws on interviews with three employees, finds that socializing for knowledge exchange is the most important knowledge management subprocess. Face-to-face meetings and on-the-job training serve as the main methods of instruction, while computer-based simulations are used as a supporting tool. Direction, socialization for knowledge discovery, and combination are more knowledge management subprocesses that can be added later to enhance KM procedures at PT XYZ.